2017
DOI: 10.1016/j.bbamcr.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Increasing extracellular Ca2+ sensitizes TNF-alpha-induced vascular cell adhesion molecule-1 (VCAM-1) via a TRPC1/ERK1/2/NFκB-dependent pathway in human vascular endothelial cells

Abstract: Increasing circulating Ca levels within the normal range has been reported to positively correlate with the incidence of fatal cardiovascular diseases (CVDs). However, limited studies have been able to delineate the potential mechanism(s) linking circulating Ca to CVD. In this study, we exposed primary human umbilical vein endothelial cells (HUVECs) and human umbilical vein cell line (EA.hy926) to different extracellular Ca to mimic the physiological state. Our data revealed that increasing extracellular Ca si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…As a pleiotropic proinflammatory cytokine, TNFα could be used to establish a model of endothelial dysfunction in vitro and in vivo 32, 33, 34, 35. Likewise, in our experiments, we found that TNFα markedly induced the expression of endothelial dysfunction biomarkers (VCAM-1, ICAM-1, and E-selectin),36, 37, 38 directly providing evidence of the important role of TNFα in endothelial dysfunction 39, 40, 41.…”
Section: Discussionsupporting
confidence: 75%
“…As a pleiotropic proinflammatory cytokine, TNFα could be used to establish a model of endothelial dysfunction in vitro and in vivo 32, 33, 34, 35. Likewise, in our experiments, we found that TNFα markedly induced the expression of endothelial dysfunction biomarkers (VCAM-1, ICAM-1, and E-selectin),36, 37, 38 directly providing evidence of the important role of TNFα in endothelial dysfunction 39, 40, 41.…”
Section: Discussionsupporting
confidence: 75%
“…Interesting, VCAM and MAPK1 were decreased in COMMD10 depleting cells in CRC cells. VCAM-1 is stimulated by TNF- α and accelerated monocyte adhesion in a NF- κ B-dependent manner ( Li et al , 2017 ). MAPK1 is involved in a wide variety of cellular processes, such as proliferation, differentiation, transcription regulation and development.…”
Section: Discussionmentioning
confidence: 99%
“…Suppressing the MAPK/NF-κB signaling pathway protects HUVECs from lipopolysaccharide-induced oxidative stress and inflammation (32). Advanced glycation end products (AGE) impair the functions of saphenous vein through the AGE receptor/MAPK signaling pathway in diabetes (43). Studies have also demonstrated that the activation of the MAPK/ERK pathway can enhance the proliferation and migration of HUVECs (44), whereas disrupting MAPK signaling pathway inhibits angiogenesis in HUVECs (45).…”
Section: Discussionmentioning
confidence: 99%